2005
DOI: 10.1091/mbc.e05-02-0131
|View full text |Cite
|
Sign up to set email alerts
|

Src and FAK Kinases Cooperate to Phosphorylate Paxillin Kinase Linker, Stimulate Its Focal Adhesion Localization, and Regulate Cell Spreading and Protrusiveness

Abstract: The ArfGAP paxillin kinase linker (PKL)/G protein-coupled receptor kinase-interacting protein (GIT)2 has been implicated in regulating cell spreading and motility through its transient recruitment of the p21-activated kinase (PAK) to focal adhesions. The Nck-PAK-PIX-PKL protein complex is recruited to focal adhesions by paxillin upon integrin engagement and Rac activation. In this report, we identify tyrosine-phosphorylated PKL as a protein that associates with the SH3-SH2 adaptor Nck, in a Src-dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
179
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(191 citation statements)
references
References 99 publications
8
179
2
Order By: Relevance
“…The recruitment of GIT proteins to adhesion sites relies on their interaction with paxillin (18,25). In nonpolarized cells, GIT2 binds to paxillin upon phosphorylation by FAK and/or Src (26). Thus, it is more than likely that the proper localization of GIT2 to sealing zones of polarized osteoclasts is determined by Src-dependent phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment of GIT proteins to adhesion sites relies on their interaction with paxillin (18,25). In nonpolarized cells, GIT2 binds to paxillin upon phosphorylation by FAK and/or Src (26). Thus, it is more than likely that the proper localization of GIT2 to sealing zones of polarized osteoclasts is determined by Src-dependent phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that merlin overexpression leads to disruption of FAK binding to its interacting partners Src and p85. The inhibitory effect of merlin on FAK activity could be either direct, as merlin has been previously shown to form a complex with FAK and NHERF (James et al, 2004), or indirect through inhibition of Rac/PAK signaling, which is known to cross-talk with FAK signaling (Hsia et al, 2003;Brown et al, 2005;Mitra et al, 2005). Indeed, we and others have previously linked merlin to Rac/PAK signaling, as PAK was found to be able to phosphorylate and inactivate merlin (Kissil et al, 2002;Xiao et al, 2002) and unphosphorylated merlin has been shown to inhibit PAK activity (Kissil et al, 2003;Hirokawa et al, 2004;Xiao et al, 2005) and Rac translocation to matrix adhesions (Okada et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Localization to focal adhesions is largely mediated by interaction of the C-terminal domain of GIT with paxillin [63][64][65]. Both GIT1 and GIT2 also bind constitutively to the Rac and Cdc42 GEF PIX (Pak-interacting exchange factor), and PIX in turn binds the serine-threonine kinase PAK (p21-activated kinase).…”
Section: Gitsmentioning
confidence: 99%